IMPLEMENTASI PASAL 36 UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI TERMINAL BANDAR RAYA PAYUNG SEKAKI KOTA PEKANBARU DIKAITKAN DENGAN UPAYA PENINGKATAN PENDAPATAN ASLI DAERAH KOTA PEKANBARU - ', SUHERDIANSYAH; Indra, Mexsasai; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The background of this research is caused by one problem. It is because indiscipline of the public transportation organizer who do not implement their obligation to visit the terminal to do their route for giving retribution so that the retribution for terminal is decreasing, because of that, the retribution source revenue is decreasing as well.The purpose of this research is to analyze the implementation of Article 36 Law Number of 22 Year 2009 about Traffic and Transportation in Bandar Raya Payung Sekaki Pekanbaru terminal, which is related by District source revenue in Pekanbaru city and can be seen from the process approached, which consists: implementation from Law, the Effort of Law, the Obstacle in The Law. The type that used by the researcher is descriptive qualitative by describing a problem, in order to know or to illustrate the event in real life has been observed or has been done with independent variable or single variable. The type of collecting data consists of primary data (interview, questioners, and direct observation) and secondary data (document books/ notes/ report and correlate policy toward the problem that been observed).The result of the research shows that the implement of Artcicle 36 has not been obeyed thoroughly, it is caused by the weakness of the regional rules to accommodate the traffic and the transportation in Pekanbaru city by do not obligate the public transportation to visit the terminal, by do not arrange the lisencing to construct the pools in the outside of the terminal. Besides, the performance of The Department of Transportation in Pekanbaru has not been maximal yet. It is proved by the fact that many violations, especially the violation which is done by the public transportation. From all the problems, they will affect to the terminal retribution, because of the public transportation does not visit the terminal, it will lead to the decreasing of terminal retribution, then the contribution to the district on revenue it selves will be the decreasing.Keywords : Traffic and Transportation ? Bandar Raya Payung Sekaki Pekanbaru Terminal ? Public Transportation